The Association of Coloproctology of Great Britain and Ireland consensus guidelines in surgery for inflammatory bowel disease. (3rd December 2018) - Brown, S. R.; Fearnhead, N. S.; Faiz, O. D.; Abercrombie, J. F.; Acheson, A. G.; Arnott, R. G.; Clark, S. K.; Clifford, S.; Davies, R. J.; Davies, M. M.; Douie, W. J. P.; Dunlop, M. G.; et al.
Abstract: Aim: There is a requirement of an expansive and up to date review of surgical management of inflammatory bowel disease (IBD) that can dovetail with the medical guidelines produced by the British Society of Gastroenterology. Methods: Surgeons who are members of the ACPGBI with a recognised interest in IBD were invited to contribute various sections of the guidelines. They were directed to produce a procedure based document using literature searches that were systematic, comprehensible, transparent and reproducible. Levels of evidence were graded. An editorial board was convened to ensure consistency of style, presentation and quality. Each author was asked to provide a set of recommendations which were evidence based and unambiguous. These recommendations were submitted to the whole guideline group and scored. They were then refined and submitted to a second vote. Only those that achieved >80% consensus at level 5 (strongly agree) or level 4 (agree) after 2 votes were included in the guidelines. Results: All aspects of surgical care for IBD have been included along with 157 recommendations for management. Conclusion: These guidelines provide an up to date and evidence based summary of the current surgical knowledge in the management of IBD and will serve as a useful practical text for clinicians performing this type of surgery.